2012
DOI: 10.1002/jbm.b.32827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cryogenic burnishing on surface integrity modifications of Co‐Cr‐Mo biomedical alloy

Abstract: Severe plastic deformation (SPD) processes have been used to modify the surface integrity properties of many materials by generating ultrafine or even nanometer-sized grains in the surface and subsurface region. These fine grained materials created by SPD and dynamic recrystallization in a thin layer near the surface usually have higher hardness and frequently exhibit enhanced mechanical properties (wear resistance, corrosion resistance, fatigue life, etc.). Cryogenic burnishing, a SPD process, was used to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…Pu et al [7] found that ultra-fine grained surface layer was formed in the burnished surface of AZ31B Mg alloy, in which the surface hardness was increased from 0.86 to 1.35 GPa and the corrosion resistance was significantly improved due to the grain refinement associated with the strong basal texture induced by cryogenic burnishing. Similar observation was made in the study of cryogenic burnishing of Co-Cr-Mo biomedical alloy by Yang et al [8]. Microstructure refinement was achieved in the burnished surface where grains of 300-600 nm size were distributed in the refined surface layers with 87% increased hardness compared to the bulk materials.…”
Section: Introductionsupporting
confidence: 55%
“…Pu et al [7] found that ultra-fine grained surface layer was formed in the burnished surface of AZ31B Mg alloy, in which the surface hardness was increased from 0.86 to 1.35 GPa and the corrosion resistance was significantly improved due to the grain refinement associated with the strong basal texture induced by cryogenic burnishing. Similar observation was made in the study of cryogenic burnishing of Co-Cr-Mo biomedical alloy by Yang et al [8]. Microstructure refinement was achieved in the burnished surface where grains of 300-600 nm size were distributed in the refined surface layers with 87% increased hardness compared to the bulk materials.…”
Section: Introductionsupporting
confidence: 55%
“…Based on some of the outlined negative aspects of the previously mentioned surface modification techniques, the researchers and scientists have realized the pressing need to develop some adequate substitutes or alternatives over the years to improve the surface properties of the biomaterials. In this relation, “subtractive manufacturing” has been proposed as one of the most influential processing methods to achieve a favorable and considerable surface modification on the surface of biomaterial/implant/device primarily via severe plastic deformation (SPD) and development of a passivating layer on the machined surface [ 75 77 ]. The process economy accompanying a massive output makes subtractive manufacturing or machining techniques such as milling, turning, and drilling the primary choice of the manufacturers.…”
Section: Surface Modification Of Metallic Implant Biomaterialsmentioning
confidence: 99%
“…Such deformation has been shown to occur in polyethylene inserts 23 and can occur in CoCrMo alloys. 24 The load we used and the geometry of the Adept hips produces a theoretical Hertzian stress of 93.5 MPa, about 21% for the yield strength (0.2% offset method)…”
Section: Cmm and Optical Measurementsmentioning
confidence: 99%